Detailed Radial Scale Height Profile of Dust Grains as Probed by Dust Self-scattering in HL Tau - Haifeng Yang; Ian W. Stephens; Zhe-Yu Daniel Lin; Manuel Fernández-López; Zhi-Yun Li; Leslie W. Looney; Rachel Harrison (The Astrophysical Journal Letters)
The vertical settling of dust grains in a circumstellar disk, characterized by their scale height, is a pivotal process in the formation of planets. This study offers in-depth analysis and modeling of the radial scale height profile of dust grains in the HL Tau system, leveraging high-resolution polarization observations. We resolve the inner disk’s polarization, revealing a significant nearside–farside asymmetry, with the nearside being markedly brighter than the farside in polarized intensity. This asymmetry is attributed to a geometrically thick inner dust disk, suggesting a large aspect ratio of H / R ≥ 0.15, where H is the dust scale height and R is the radius. The first ring at 20 au exhibits an azimuthal contrast, with polarization enhanced along the minor axis, indicating a moderately thick dust ring with H / R  ≈ 0.1. The absence of the nearside–farside asymmetry at larger scales implies a thin dust layer, with H / R  < 0.05. Taken together, these findings depict a disk with a turbulent inner region and a settled outer disk, requiring a variable turbulence model with α increasing from 10 ^−5 at 100 au to 10 ^−2.5 at 20 au. This research sheds light on dust settling and turbulence levels within protoplanetary disks, providing valuable insights into the mechanisms of planet formation.